2021
DOI: 10.1021/acs.joc.1c01789
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spiro[chromene-imidazo[1,2-a]pyridin]-3′-imines via 6-exo-dig Cyclization Reaction

Abstract: A transition-metal-free postmodification of the Groebke–Blackburn–Bienaymé (GBB) reaction for the synthesis of spiro­[chromene-imidazo­[1,2-a]­pyridin]-3′-imine was discovered. The unusual transformation represents the first example of activation and the reaction of the imidazole carbon atom. In this postcondensational modification, KOt-Bu acts as a base, which, after the isomerization of an alkyne moiety to allene, causes the next unique nucleophilic reaction of the imidazole carbon atom that results in spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Recently, we demonstrated an undergraduate laboratory experiment wherein GBB-MCR-derived products were synthesized via in situ generated isocyanides from N -formylamines . The diverse fused heterocycles generated via GBB reaction include bicyclic imidazo­[1,2- a ]­pyridine, imidazo­[1,2- a ]­pyrimidine, imidazo­[1,2- a ]­pyrazine, imidazo­[2,1- b ]­thiazole, imidazo­[2,1- b ]­[1,3,4]­thiadiazole, imidazo­[1,2- b ]­[1,2,4]­triazole, imidazo­[1,2- b ]­pyrazol, and imidazo­[2,1- b ]­oxazole. Various polycyclic scaffolds (1–11, Figure ) are also synthesized via post modification of the GBB-derived products. , Recently, we demonstrated that the one-pot-derived GBB products can be elaborated to fused polycyclic heterocycles (12–14) involving Pictet–Spengler cyclization (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated an undergraduate laboratory experiment wherein GBB-MCR-derived products were synthesized via in situ generated isocyanides from N -formylamines . The diverse fused heterocycles generated via GBB reaction include bicyclic imidazo­[1,2- a ]­pyridine, imidazo­[1,2- a ]­pyrimidine, imidazo­[1,2- a ]­pyrazine, imidazo­[2,1- b ]­thiazole, imidazo­[2,1- b ]­[1,3,4]­thiadiazole, imidazo­[1,2- b ]­[1,2,4]­triazole, imidazo­[1,2- b ]­pyrazol, and imidazo­[2,1- b ]­oxazole. Various polycyclic scaffolds (1–11, Figure ) are also synthesized via post modification of the GBB-derived products. , Recently, we demonstrated that the one-pot-derived GBB products can be elaborated to fused polycyclic heterocycles (12–14) involving Pictet–Spengler cyclization (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…14 For example, a transitionmetal-free synthesis of spiro[chromene-imidazo[1,2-a]pyridin]-3′-imines was discovered by a post-GBB/6-exo-dig cyclization reaction under mild conditions. 15 Subsequently, Stahlberger and co-workers have developed a sequential synthesis route toward annulated imidazo [4,5-c]isoquinolines via a novel GBB-3CR/ imidoylative Hartwig−Buchwald amination sequence. 16 In the past decades, isocyanides and azides have been known as versatile synthetic intermediates in organic synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, various post-condensation transformations of the GBB-3CR have become a powerful method in the synthesis of structurally diverse heterocyclic compounds . For example, a transition-metal-free synthesis of spiro­[chromene-imidazo­[1,2- a ]­pyridin]-3′-imines was discovered by a post-GBB/6- exo -dig cyclization reaction under mild conditions . Subsequently, Stahlberger and co-workers have developed a sequential synthesis route toward annulated imidazo­[4,5- c ]­isoquinolines via a novel GBB-3CR/imidoylative Hartwig–Buchwald amination sequence .…”
Section: Introductionmentioning
confidence: 99%
“…The previous observations and following our long-lasting interest in applying different types of isocyanides, 12 led us to design and synthesize a new class of functionalized isocyanides with an alkyne moiety. With the suitable choice of other components in the Groebke–Blackburn–Bienaymé (GBB) reaction, we wish to access the unprecedented 6/7/5-fused heterocyclic skeletons through intramolecular transition-metal-free double hydrofunctionalization (hydroamination and hydroalkoxylation) of nonactivated alkyne, which was completed upon preparative thin layer chromatography (PTLC) on silica gel plate.…”
mentioning
confidence: 99%